Pengaruh Review Produk dan Content Creator Terhadap Minat Beli Melalui Affiliate Marketing pada Pengguna E-Commerce Shopee - Ayu Luthfiani, Dyah; Arqy Ahmadi, Mirzam (Teewan Journal Solutions, 2025)
In today's digital era, consumers are increasingly selective in receiving information, especially when choosing products on e-commerce platforms like Shopee. Product reviews and the role of content creators are important elements influencing consumer purchase intentions. This study aims to understand how product reviews and content creators influence purchase intentions through affiliate marketing programs among Shopee users. The method used in this research is a qualitative approach with literature review analysis. The sample was taken from various related literature and scholarly articles. The measurement tool used is narrative analysis of the data collected from these sources. The results of the study show that honest and informative product reviews, along with credible content creators, play a crucial role in building consumer trust, ultimately increasing purchase intention. The discussion also emphasizes that in addition to product reviews and content created by content creators, other factors such as price promotions and recommendations from friends or family also influence purchasing decisions. However, this research has several limitations, such as the sample being limited to literature, which may not fully represent direct consumer experiences. Future research is expected to include interviews or surveys with direct consumers to obtain more in-depth data.